Investigating the Influence of Social Support Factors on Retention of Boys in Public Secondary Schools in Marsabit County - Aga, Safina Mohammed; Mwirichia, Severina Mwirichia; Murithi, Sabina Murithi (Journal of Education and Practice, 2022)
Purpose: To investigate the influence of social support factors on retention of boys in public secondary schools in Marsabit county. Methodology: The research design used was mixed methodology because there was an application of both quantitative and qualitative methods when collecting data. The study was located in Marsabit County. The target population was 8 secondary schools in Marsabit County that had boys' students in them. That is both boys' secondary schools and mixed secondary schools. The respondents were 56 class teachers, 4,559 boys' students and 48 parents present at Board of Management. Class teachers and parents were selected using simple random sampling method with an application of Krejcie & Morgan table or formular to obtain 48 and 42 class teachers and parents respectively. The sample technique that was used on students was determined using a Kothari statistical method to obtain a sample of 94. Questionnaires and interview guides were answered by students, teachers and parents respectively. The pre-test study was conducted in two public secondary school in Isiolo which were Isiolo boys' secondary school and Garbatula mixed day secondary school whose respondents comprised of 5 class teachers, 10 students and 4 parents at BOM. Reliability and validity were also measured. The conclusion made was that a lot of boys failed to remain in school since they lacked motivation from the people surrounding them. That is, most of the boys' peers, teachers and parents did not adequately portray clear need on why they should remain in school. The results were presented using tables and explanation. Results: As per the questionnaire, 46(60%) strongly agreed and 17(22%) agreed that parents were so supportive to their completion of secondary school education (Median-5). Additionally, 23(29%) strongly agreed and 39(51%) agreed that the community has always wished students well in academic endeavors and are always present when needed (Median-4). Nevertheless, 53(69%) strongly disagreed and 14(18%) disagreed that the school had provided conducive classes and meals among other resources to the students (Median-2). Additionally, 39(51%) strongly disagreed and 33(42%) agreed that the government had provided reliable and qualified teachers who were committed to see students succeed in secondary education (Median-2). The study interviewed teachers and parents of public secondary schools of Marsabit County. The type of support accorded to the boys to remain in school included moral support to shape their manners, financial support to provide schools fees; religious support to check their status with God; and counseling support to offer advice and listening ear to the issues boys underwent through. The ways through which social support was administered included assignments to do at home hence keeping them busy while the parents indicated that they offered them tasks such as cleaning houses, utensils, taking care of the cattle, assisting them in running the businesses and sending them to library to keep them busy. Further, the motivating factors that were put in school which attract students to remain in school included different meals; flexible curriculum hence a choice to choose favorable 8 subjects; school uniform and books; library; entertainment days; school clubs; and cocurricular activities such as drama, soccer, rugby, basketball, tennis and badminton. Unique contribution to theory, policy and practice: Most secondary school management were struggling in ensuring that students have decent learning classes and eat frequently in school. That notwithstanding, the students did not have teachers who would be committed in ensuring that they instill discipline and ensure that the boys are interest in education matters and school activities in general. The recommendations made on social support is that secondary school principals should liaise with the ministry of education for requests to have as many teachers as possible. This is because, when teachers are present, students will benefit a lot since they would be taught and be more confident towards excelling in the examinations. Additionally, the government should increase budgetary allocation to the ministry of education to be able to fund education in the marginalized regions adequately. The fund would be used to build classes and provide at least a meal per day. The ministry of education officials in Marsabit, should incorporate the idea of building classes using affordable means such as precast panels and fabricated panels. This method would cut cost to manageable limits based on the allocated and available funds.